2005
DOI: 10.1016/j.cell.2005.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Physical Association and Coordinate Function of the H3 K4 Methyltransferase MLL1 and the H4 K16 Acetyltransferase MOF

Abstract: A stable complex containing MLL1 and MOF has been immunoaffinity purified from a human cell line that stably expresses an epitope-tagged WDR5 subunit. Stable interactions between MLL1 and MOF were confirmed by reciprocal immunoprecipitation, cosedimentation, and cotransfection analyses, and interaction sites were mapped to MLL1 C-terminal and MOF zinc finger domains. The purified complex has a robust MLL1-mediated histone methyltransferase activity that can effect mono-, di-, and trimethylation of H3 K4 and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
629
2
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(668 citation statements)
references
References 51 publications
32
629
2
5
Order By: Relevance
“…During the formation of this complex, MLL is cut by taspase into an N-terminal (MLL N ) and a C-terminal (MLL C ) fragment. 25 MLL C then associates with at least four proteins, that is, the histone acetyltransferase MYST1(MOF), 26 and WDR5, RBBP5 and ASH2L, to ensure histone modification and methyltransferase activity. 27 The MLL N fragment has a binding site for MEN1 at the N-terminal end and both recruit PSIP1(LEDGF).…”
Section: Etiology Of Mll Rearrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the formation of this complex, MLL is cut by taspase into an N-terminal (MLL N ) and a C-terminal (MLL C ) fragment. 25 MLL C then associates with at least four proteins, that is, the histone acetyltransferase MYST1(MOF), 26 and WDR5, RBBP5 and ASH2L, to ensure histone modification and methyltransferase activity. 27 The MLL N fragment has a binding site for MEN1 at the N-terminal end and both recruit PSIP1(LEDGF).…”
Section: Etiology Of Mll Rearrangementsmentioning
confidence: 99%
“…MLL N also contains a CxxC domain, which specifically binds to unmethylated DNA. 29 Transcription factors such as p53 and CTNNB1(b-catenin) are most likely to recruit the MLL complex to initiate RNA synthesis, 26,30 and specific genes, such as the HOX genes, seem to be more dependent on the MLL complex for chromatin modification during transcription than others. 31,32 In MLL rearrangements the breakpoint in MLL is highly conserved and all fusion partners are fused in frame, leading to a gain of function of the MLL complex.…”
Section: Etiology Of Mll Rearrangementsmentioning
confidence: 99%
“…It is now known that MYST proteins have important roles in various biological processes (Ceol and Horvitz, 2004;Kusch et al, 2004;Dou et al, 2005;Smith et al, 2005;Mendjan et al, 2006;Sykes et al, 2006;Tang et al, 2006). These enzymes have been the subjects of several excellent reviews Squatrito et al, 2006;Avvakumov and Coˆte´, 2007;Lafon et al, 2007;Rea et al, 2007;Thomas and Voss, 2007).…”
Section: Identification Of Moz Morf and Other Mystic Hatsmentioning
confidence: 99%
“…This complex localizes to hundreds of sites along the male Xchromosome and is required to equalize X-linked gene expression between male flies, with one X-chromosome and female flies with two. Recent biochemical purifications revealed that both the Drosophila and mammalian MOF proteins reside in multi-protein complexes and that most of these interacting proteins are conserved between Drosophila and mammals (Table 2; Dou et al, 2005;Smith et al, 2005;Mendjan et al, 2006). Co-purification of four human MSL proteins (hMSL1, hMSL2, hMSL3 and hMOF) showed that the MSL (Borrow et al, 1996;Carapeti et al, 1998;Champagne et al, 1999Champagne et al, , 2001Chaffanet et al, 2000;Kitabayashi et al, 2001;Pelletier et al, 2002;Bristow and Shore, 2003;Deguchi et al, 2003;Kindle et al, 2005;Katsumoto et al, 2006;Thomas et al, 2006;Ohta et al, 2007 Abbreviation: HAT, histone acetyltransferases.…”
Section: The Histone Acetyltransferase Mofmentioning
confidence: 99%